Comparative Framework between Peruvian and Spanish Environmental Assessment Regulation: Deficiencies, Similarities, and Opportunities for Change - Barahona, Jesús (Revista de Derecho, 2025)
The aim of this paper is to use a comparative study with Spanish legislation to highlight the main scope and instruments of the national environmental impact assessment procedure and system (SEIA) in a context of technological evolution and climate emergency. With the European legal system as a guide, the aim is not only to identify the strengths of our regulations, but also to detect regulatory gaps and provisions that are ineffective and incompatible with the aforementioned context. In this way, based on empirical evidence and comparative law experience, the reader will be invited to reflect and, raising the need to initiate a feedback process, we will offer a series of proposals for regulatory improvement in order to adapt the provisions of the SEIA to an era where, on the one hand, exponential scientific and technological progress prevails and, on the other, the warning of a climate emergency era arises.